Thomas B. Edsall on the Convicted Felon Trump, and Walter J. Ong’s Thought - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2024)
In my wide-ranging 3,300-word essay, I first briefly introduce the life and work of the American Jesuit Renaissance specialist and cultural historian and pioneering media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955). Then I discuss Thomas B. Edsall’s op-ed column “Trump Would Be Long Gone if Only We Could . . . ” (dated June 12, 2024) in the New York Times.